Rancang Bangun Dashboard Untuk Visualisasi Kinerja Penelitian Dan Pengabdian Masyarakat (Studi Kasus Institut Bisnis Dan Informatika STIKOM Surabaya) - Hermawan, Thony; Wurijanto, Tutut; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
The Institute of Business and Informatics Stikom Surabaya as one of the collages in Indonesia is obliged to carry out the Tri Dharma Perguruan Tinggi, that were education, research, and community Service. In the activities of research and community service, The Institute of Business and Informatics Stikom Surabaya has formed department that called Penelitian dan Pengabdian Masyarakat (PPM). The problems that occurs was PPM Department hasn’t media for monitoring performance and also have experienced complication in collecting data because of two separate data sources from The Institute of Business and Informatics Stikom Surabaya and the Directorate of Higher Education (Dikti). Dikti provides facility in the form of a web service portal Management Information System for Research and Community Service (SIM-LITABMAS) to retrieve data on research and community service. The solution offered is to build a dashboard that can display performance information visually of PPM Department in accordance with performance indicators. Additionally to build a system that can synchronize data with SIM-LITABMAS via web service. The research proves that through performance dashboard for research and community service has been created, PPM Department can synchronize data with web service of SIM-LITABMAS and than see the performance of PPM Department interactively according to performance indicators.